Education Process Digitalization in Sociocultural Activity Managers’ Training - Lubarets, Vladislava; Pavlenko, Dmitro; Litvinova, Tetyana (Journal of Education, Technology and Computer Science, 2020)
The process of the future sociocultural activity managers’ professional training under the conditions of information and educational environment in the higher education institutions is recreational-aesthetic and psychological-rehabilitative restoration of the future specialists’ intellectual and professional potential, which can be effectively applied in the different spheres of life.